Perceived Insider Status and Feedback Reactions: A Dual Path of Feedback Motivation Attribution - Chen, Xiao; Liao, JianQiao; Wu, Weijiong; Zhang, Wei (Frontiers in Psychology, 2017)
Abstract Many studies have evaluated how the characteristics of feedback receiver, feedback deliverer and feedback information influence psychological feedback reactions of the feedback receiver while largely neglecting that feedback intervention is a kind of social interaction process. To address this issue, this study proposes that employees’ perceived insider status (PIS), as a kind of employee-organization relationship, could also influence employees' reactions to supervisory feedback. In particular, this study investigates the influence of PIS focusing on affective and cognitive feedback reactions, namely feedback satisfaction and feedback utility. Surveys were conducted in a machinery manufacturing company in the Guangdong province of China. Samples were collected from 192 employees. Data analysis demonstrated that PIS and feedback utility possessed a U-shaped relationship, whereas PIS and feedback satisfaction exhibited positively linear relationships. The analysis identified two kinds of mediating mechanisms related to feedback satisfaction and feedback utility. Internal feedback motivation attribution partially mediated the relationship between PIS and feedback satisfaction but failed to do the same with respect to the relationship between PIS and feedback utility. In contrast, external feedback motivation attribution partially mediated the relationship between PIS and feedback utility while failing to mediate the relationship between PIS and feedback satisfaction. Theoretical contributions and practical implications of the findings are discussed at the end of the paper. Key words： Perceived Insider Status (PIS), Feedback Reactions, Feedback Motivation Attribution.